Penetapan Target Penjualan Produk Aki pada PT. X - Felicia Sanjaya; Prayonne Adi (Jurnal Titra, 2018)
PT.X is field of industrial equipment, office equipment, automotive, workshop equipment, building, and safety equipment. One of the new products sold by the company is a battery product, which was recently sold in December 2017. The company determined a sales target 0.1% of the market demand, but in fact the company only made 0.0078% of the market. The company aims to set the sales target of battery products by taking into account several factors such as advertising, exhibitions, and number of vehicles. New sales target will be used by the company to measure success rate of the company work program thas has been established.